Dangerous people and places : a community newspaper's constructions of crime - Raymond, Leigh Alice (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2014)
This thesis argues that there is a clear imbalance in the representation of crime in the newspaper, Grocott's Mail, in Grahamstown, in the Eastern Cape of South Africa. The thesis concludes that the system of marginalisation and segregation which was established during the apartheid era is the foundation for the continued segregation and marginalisation of certain groups of people in Grahamstown as depicted in crime journalism. Previous research shows that not only people, but spaces are marginalised through media representations of crime. As people are represented as dangerous, so too the spaces they occupy become dangerous spaces. Importantly, the research shows that discourses of marginalisation are present in newspaper reports reproducing the discourses prominent in society, and in turn, the newspaper itself perpetuates these marginalising discourses. This extends into the coverage that different crimes receive in newspapers. For instance, the reports show that a middle-class audience will be more concerned with property crime in middle-class neighbourhoods, than other crimes in lower-class neighbourhoods. I argue that not only the type of crime, but the severity, the effect, and the necessity for justice represented by the newspaper, are all largely determined by the region of the crime. Further, I show that the criminal is not only demonised and represented as individually deviant in the reports in the newspaper, but that these representations are made by this newspaper because they are deeply imbedded as a discourse in society. This is partly because this newspaper has taken on a monitorial role, requiring neutral reporting from journalists, and a dedication to surveying the processes of state institutions, like the police and courts. As a result, the ways in which crime is reported on in the newspaper is fairly well fixed, making it difficult for journalists to conceive of different ways of reporting crime. The representations of the criminal justice system that the monitorial media, this newspaper included present, are a careful balance between the interest of the public, and the need to preserve relationships with sources. The monitorial media in general, and this newspaper in particular, represent the criminal justice system. The relationship between the police and the newspaper, and the courts and the media, therefore strongly influences the way in which crime news is reported. In particular, crime news is represented from the perspective of the criminal justice system. This research was carried out using Critical Discourse Analysis, qualitative interviews, and focus group interviews.
Keywords: Grocott's Mail (Grahamstown, -- South Africa); Community newspapers -- South Africa -- Grahamstown; Crime and the press -- South Africa -- Grahamstown; Newspapers -- Objectivity; Mass media policy -- South Africa -- Grahamstown; Social responsibility of business -- South Africa -- Grahamstown; Police and the press -- South Africa -- Grahamstown